Synthesis and Thermal Stability of Palladium Nanoparticles Supported on γ-Al2O3 - Kalishyn, Yevhen Y.; Ordynskyi, Vladislav V.; Ishchenko, Mykola V.; Bychko, Igor B.; Kaidanovych, Zinaida V.; Trypolskyi, Andrii I.; Strizhak, Peter E. (Current Nanomaterials, 2020)
Background: Deposition of palladium nanoparticles from colloidal solution on various supports produces palladium catalysts with a predetermined size and concentration of the palladium nanoparticles, which allows to study the nanoparticle size effects and support influence on palladium catalytic properties. Objective: The goal of the present work was the development of a preparation method of systems supported on γ-Al2O3 palladium nanoparticles with a controlled size and determination of their thermal stability in oxidizing and reducing atmospheres. Methods: We demonstrated the preparation of Pd/γ-Al2O3 composite by precipitation of the size-controlled palladium nanoparticles with a narrow size distribution from colloidal solution. The composites were characterized by X-ray diffraction (XRD), and transmission electron microscope (TEM) methods. Results: The size and size distribution of the nanoparticles supported on γ-Al2O3 were found to be increasing upon precipitation due to strong Pd/γ-Al2O3 interaction. A significant enlargement of the supported nanoparticles occured at 300°C. The aggregation of the nanoparticles was observed at temperatures above 500°C resulting in an increase in their size. Conclusions: Our findings are not only applicable for the preparation of a model Pd supported on the γ-Al2O3 catalyst but could be applicable to the designing of the Pd-containing catalyst for important industrial high-temperature processes.
Keywords: catalysis